Sentinel lymph node biopsy with blue patent more imprinted in the axillary stage of breast cancer in a hospital of high complexity - Yan-Quiroz, Edgar Fermin (2021)
Objetive: To analyze the main clinical-pathological characteristics of patients with breast carcinoma in whom a sentinel lymph node biopsy was performed with patent blue plus imprint in the axillary staging. The study. This descriptive series evaluated a series of 20 cases of patients with an anatomopathological diagnosis of infiltrating ductal carcinoma treated in the area of ​​Oncological Surgery of the Hospital of High Complexity "Virgen de la Puerta" EsSalud, La Libertad - Peru, during the period February 2017 until January 2018. Findings: The sensitivity and specificity of the sentinel lymph node imprint was 75% respectively. The positive and negative predictive value was 67% and 82% respectively. The positive and negative likelihood ratio was 3.0 and 0.33. The Kappa index was 0.2 of considered as a concordance index. Conclusions. The sentinel lymph node technique is a good alternative for the management of breast cancer, since it avoids unnecessary surgical interventions.